The Effect of the Pair Checks Model on Learning Outcomes and Critical Thinking Ability in Elementary School - Cicilia Ovavia; Sufyarma Sufyarma; Atmazaki Atmazaki; Yalvema Miaz (AL-ISHLAH: Jurnal Pendidikan, 2022)
The research aims to review (1) the impact of the Pair Checks type cooperative learning model on students' thinking ability compared to conventional lessons in thematic lessons of fourth-grade elementary school, (2) the impact of the Pair Checks model on student achievement compared to conventional lessons in fourth-grade thematic lessons of elementary school, (3) the thinking ability of students who are taught based on the cooperative model of the Pair Checks type are high compared to the thinking ability of the students who are taught based on conventional learning, and (4) the relationship between learning achievement and thinking ability seen from the cooperative model of the type of Pair Checks. The critical thinking ability studied is critical thinking ability taught in an integrated manner. The place of research is SDN 08 Mandeh. The research method used was quasi-experimental with design research in One group pre-test and post-test design. The sample applied was class IVA, with 23 students. The information was collected by using a written exam. The data obtained are as follows (1) the thinking ability of students who apply the cooperative model are significantly higher than the thinking ability of students in learning using conventional methods because there is T_count = 1.78 T_table = 1.68 until H_0 is rejected and H_1 is accepted, (2) student achievement in learning that applies the cooperative model is significantly higher than student learning outcomes in learning using conventional methods because there are T_count = 2.02 T_table = 1.68 until H_0 is rejected and H_1 is accepted, (3) critical thinking ability of students are being taught based on the Pair Checks model, it is higher than the thinking ability of students in conventional lessons because based on low initial knowledge at a level of 0.05, it is found that T count T table with 0.178 1.68 until H0 is rejected and H1 is accepted, and (4) there is a relationship between learning achievement and students' thinking ability on the pair checks model because there is a significant effective contribution between learning achievement and thinking ability with a percentage of 87.6% and the remaining 12.4 is influenced by other factors.